2020
DOI: 10.1186/s41983-020-00210-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc and copper levels in a sample of Egyptian epileptic children

Abstract: Background: Epilepsy is among the most common disabling neurological disorders among children. Altered serum levels of zinc and copper may facilitate seizure occurrence and repetition, and antiepileptic drugs may disturb their serum levels affecting disease control and outcome. Objective: To investigate the association between serum levels of zinc and copper and epilepsy and antiepileptic treatment in a group of Egyptian epileptic children. Methods: Case-control study on 100 epileptic patients, aged from 2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…As evidenced in our study by significantly higher TAC and lower zinc serum levels among pediatric patients with newly diagnosed epilepsy compared to healthy controls, epileptic seizures induced oxidant generation stimulate the body’s antioxidant defense mechanisms in an attempt to balance the oxidants’ effect, resulting in high TAC serum levels with consumption of antioxidant trace elements such as zinc. In line with our findings, Eissa et al [ 51 ] reported significant lower levels of serum zinc in a sample of Egyptian epileptic children. Similary, Farahani et al [ 52 ] and Talat et al [ 53 ] reported similar results.…”
Section: Discussionsupporting
confidence: 93%
“…As evidenced in our study by significantly higher TAC and lower zinc serum levels among pediatric patients with newly diagnosed epilepsy compared to healthy controls, epileptic seizures induced oxidant generation stimulate the body’s antioxidant defense mechanisms in an attempt to balance the oxidants’ effect, resulting in high TAC serum levels with consumption of antioxidant trace elements such as zinc. In line with our findings, Eissa et al [ 51 ] reported significant lower levels of serum zinc in a sample of Egyptian epileptic children. Similary, Farahani et al [ 52 ] and Talat et al [ 53 ] reported similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Also, this was in disagreement also with Eissa et al, [13] who found no statistical significance on measuring the copper serum level between patients group when compared to the control group.…”
Section: Discussionmentioning
confidence: 53%
“…The mean of serum zinc concentration in these studies ranged from 57 up to 117.4 μg/dL. [21][22][23] These differences and wide variations between studies regarding serum zinc level may be due to its normal physiological fluctuations; serum zinc level fluctuate by about 20% throughout the day, mostly because of the ingestion of food. After meals, there was immediate increase in serum zinc concentration, after which this concentration decreases for 4 hours and then increase again.…”
Section: Discussionmentioning
confidence: 81%